HOMOLOGATION RECONSTRUCTION IN BANKRUPTCY THAT IS BASED ON DIGNIFIED JUSTICE - Agus Winoto; Teguh Prasetyo; Amin Purnawan (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Law No 37 Year 2004 on Bankruptcy and Liability Payment Postponement (PKPU) enables a debtor to come up with a settlement offer to the creditor, prior to or after bankruptcy, in order to pay for liabilities or end bankruptcy and PKPU. A settlement offer from a debtor, discussed and submitted after liability verification, which has been agreed and approved by both the debtor and the creditor must first be legalized by a panel of judges that decide on the case. This will give the settlement offer a fixed and binding legal status. Hence, it can be executed. However, the panel of judges do has the right to legalize a settlement offer agreed and approved by both the debtor and the creditor, as stipulated in Article 159 subsection (2) and Article 285 subsection (2) of Law no 37 Year 2004. This right to deny legalizing a settlement offer is against the universal principles of agreement, especially concerning mutual agreement, pactasuntservanda, freedom of contract, and common justice. The issues discussed in this research include (1) Why legalizing a settlement in the bankruptcy law does not reelect justice? (2) What are the consequences of legalizing a settlement in the bankruptcy law that does not reflect justice? (3) What is the law construction for legalizing a settlement in the bankruptcy law that is based on the values of justice? The method employed was judicial sociology. Data were collected from interviews, observations, and documentations. Those data were then analyzed using the interactive analysis method.  Results show that (1) Legalizing a settlement in both the bankruptcy law and PKPU is not yet based on justice values, especially the value of dignified justice based on Pancasila, namely Principles, 2, 4, and 5. (2) Hindrances in legalizing a settlement among others are; the agreement between a debtor and all creditors or most/the majority of creditors in a settlement offer is not recognized by the panel of judges; It is against the universal principles of agreement, especially the freedom of contract, the principle of pactasuntsevanda, and mutual agreement, and it does not recognize the deliberation between both the debtor and creditors, which is presided by a curator and a supervising judge and is in line with Principle 4 of Pancasila. (3) There needs to be a reconstruction for the ideal values of legalizing a settlement in bankruptcy law and PKPU, based on the values of dignified justice, that is aimed at protecting all parties involved in the settlement and PKPU.  Keywords: legalizing a settlement, bankruptcy law, PKPU, dignified justice